Possible Anti-asthmatic Effect of Iraqi Ammi majus Seeds Extract Induced by Ovalbumin in Mice - Younis, Zainab T; Mutlag, Shihab H (The Iraqi Journal of Veterinary Medicine, 2022)
Asthma is a chronic and complex condition of the respiratory tract, that occurs in both children and adults. Currently available medications have side effects; therefore, new therapies with fewer side effects are needed. Thus, present study was designed to evaluate the potential anti-asthmatic effects of alcoholic extract of Ammi majus on ovalbumin-induced asthma in mice. Forty-eight female Albino mice were randomly assigned to one of six groups with 8 animals each. Group I received distilled water as a negative control, Group II received ovalbumin as a positive control, Groups III and IV received Ammi majus orally at 64 and 128 mg/kg/day, respectively, with sensitization, and Groups V and VI received Ammi majus orally at 64 and 128 mg/kg/day, respectively, without sensitization. Bronchoalveolar lavage fluid (BALF) was obtained 24 h after the 1st challenge to measure the number of inflammatory cell counts. In addition, lung tissue was removed for histopathological examination. Oral administration of alcoholic extract of Ammi majus at both doses (64 and 128 mg/kg) significantly inhibited ovalbumin-induced increases in total and differential cell counts of eosinophile, neutrophile, monocyte, and lymphocyte) in BALF, in addition, improve histopathologic events of asthma in lung tissue of ovalbumin-induced asthma in mice. These results demonstrated that Ammi majus alcoholic extract has a potent anti-asthmatic activity that improved ovalbumin-induced asthma.